KONSEP KESELAMATAN DALAM AL-QURAN - Susanti, Salamah Eka (Humanistika : Jurnal Keislaman, 2018)
Salamah Eka SusantiÂ Abstract: The doctrine of salvation is an important concept that is common to every religion. Therefore, each religion claims to be the savior (Salvator) for each of its followers. In Protestant Christianity for example, there is a doctrine known as "No Salvation Outside Christianity", beyond Christianity there is no salvation. Likewise in Catholic Christianity, adhering to, a doctrine that mentions "Extra Ecclesiam Nulla Salus", outside the church there is no salvation. For Judaizers, the doctrine of "The Chosen People" becomes their theological foundation that only Jews will gain salvation. Whereas in Islam itself, the theological argument of salvation as their own is based on the doctrine of ultimate cessionism (ie, Christianity and Judaism) remains valid before the coming of the new (Islamic) rule that replaces the old rule, the new rule by itself cancel the previous rule. This argument is based primarily on the verse (Ø¥Ù Ø§ÙØ¯ ÙÙ Ø¹ÙØ¯ Ø§ÙÙÙ Ø§ÙØ§Ø¡ Ø³ÙØ§Ù) .If historically examined, all religions without exception, both tertiary and non-theistic are born and have a claim to the truth about the assurance of salvation, whether expressed explicitly or implicitly. In other words, no religion does not have a doctrine of salvation because the claim of salvation is something that is already inherent in every religion.Keywords: Concepts, Salvation, Al-Quran.Â